PEMEROLEHAN FONOLOGI DAN METATESIS: STUDI KASUS PADA ANAK USIA 2 TAHUN 10 BULAN - Anggaira, Aria Septi (Universitas Pendidikan Indonesia, 2016)
Abstract This study aimed to describe the phonemes produced by children aged 2 years and 10 months and describes forms of exchange or metathesis sound that occurs in producing the sounds of language in words. The data collection technique use three stages of strategic sequence. These stages are (1) a method of providing data, (2) data analysis methods, and (3) methods of presenting the results of the analysis. Data in the form of speech is transcribed into a phonetic transcription. The findings of this research are: The respondent has been able to produce almost any sounds or phonemes that exist in Indonesian. Phonemes produced consisting of consonant phonemes that are already emerging that a total of 18 phonemes: / b /, / t∫ /, / d /, / g /, / d /, / dj /, / k /, / l /, / m /, / n /, / ŋ /, / ñ /, / p /, / r /, / s /, / t /, / w /, / y /. From the 18 consonant phonemes are emerging, 8 of them have variations, so that the number of phonemes is generated as a whole is 27 consonant phonemes. Respondents have been able to produce six vowel phonemes plus two variations so that all amount to 8 vowel phonemes. It was found five pieces of diphthongs are: / au /, / ai /, / ei /, / o /, and / ua /. In the span of less than one month found 19 words that contain elements of metathesis. From the 19 words, found 5 types or form of an exchange of sounds and sound accompaniment of addition and subtraction. Keywords: language acquisition, phonology, metathesis, phonemes.